A wrench in the works : a fixer-upper mystery - Carlisle, Kate, 1951- (Carlisle, Kate, 1951- Fixer-upper mystery, 2018)
Shannon Hammer's younger sister Chloe left Lighthouse Cove after high school to make it big in Hollywood. And she did it! For several years now, Chloe has been the co-host of a popular home repair show on the Do-It-Yourself Network. Now, after ten years, Chloe returns to Lighthouse Cove with her crew and co-host to film several shows featuring her sister Shannon, along with some special mini-segments on Victorian style and design. But Shannon realizes quickly that things are not exactly blissful in TV land. Her sister's handsome co-host is being stalked by someone who turns out to be his estranged wife, Erica--who also happens to be the executive producer of the show. Erica's got a knack for stirring up sticky situations and when she's found dead, Chloe and the entire crew are under suspicion. Shannon soon discovers the real reason why Chloe was so eager to move away from Lighthouse Cove all those years ago. Can Shannon figure out if that ten-year-old secret is connected to Erica's death? And can she track down the real killer before her beloved sister becomes the next victim?